Disproportionation-induced solid-state fluorescence in 6, 13-dihydropentacenes. Issue 30 (31st May 2019) - Tajima, Tomoyuki; Sanda, Rai; Nishihara, Katsuya; Shirai, Hitoshi; Okuda, Yasuhiro; Orita, Akihiro; Takaguchi, Yutaka
Abstract : The thermally and photolytically induced disproportionation of 6, 13-dihydropentacene derivatives into tetrahydropentacenes and pentacenes results in unique solid-state fluorescence. Abstract : The thermally and photolytically induced disproportionation of 6, 13-dihydropentacene derivatives into tetrahydropentacenes and pentacenes results in unique solid-state fluorescence. The fluorescence thereby depends on the molecular structure and the molecular arrangement in the solid state.